2010
DOI: 10.14295/bds.2009.v12i1.248
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes técnicas de acabamento e polimento sobre a rugosidade superficial de resinas acrílicas utilizadas para restaurações provisórias

Abstract: Considerando a importância da lisura superficial das restaurações provisórias, o objetivo desse trabalho foi de avaliar o efeito de diferentes métodos de acabamento e polimento sobre a rugosidade superficial de 05 resinas acrílicas autopolimerizáveis(Dencor®, Dencrilay®, Duralay®, Instatemp® e Vipi Cor®). Um total de 200 corpos de prova foram confeccionados, sendo 40 corpos de prova para cada resina, que foram obtidos a partir de uma matriz bipartida com ummolde cilíndrico de aço inoxidável de 10 mm de diâmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In another study 31 , there were also no significant differences in the roughness of the acrylic resins Dencor, Duralay and Vipi Cor. The study of Şen et al 3 showed that the methacrylate-based resin specimens showed smoother surfaces than the bis-acrylic composite specimens.…”
Section: Discussionmentioning
confidence: 86%
“…In another study 31 , there were also no significant differences in the roughness of the acrylic resins Dencor, Duralay and Vipi Cor. The study of Şen et al 3 showed that the methacrylate-based resin specimens showed smoother surfaces than the bis-acrylic composite specimens.…”
Section: Discussionmentioning
confidence: 86%
“…For this reason, temporary prostheses should be perfectly in accordance with what is desired of the definitive prosthesis. In view of this, the surface of these temporary restorations should be polished to avoid accumulation of biofilm, as well as to provide comfort for the patient and be esthetically acceptable 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, in order to avoid the loss of prosthetic pillars and adjacent teeth to periodontal disease or caries, smooth well-finished parts are extremely important, in addition to making the element esthetically acceptable [6][7] . Thus, finishing and polishing techniques need to be established reconciling the use of accessible materials, reduction in clinical time and the attainment of less surface roughness 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For each step, each specimen was polished for 10 seconds, six times per specimen, at 3,000 rotations per minute 18 . The pumice stone and Spain white pastes were prepared in the proportion of 5.0 g to 1 ml of water.…”
Section: Protocols Proposed For the Removal Of Stainsmentioning
confidence: 99%